FORMULATION AND EVALUATION OF DASATINIB LOADED SOLID LIPID NANOPARTICLES - Begum, M. Yasmin; Gudipati, Prathyusha Reddy (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: The aim of present work was to formulate and evaluate Dasatinib (DST) loaded solid lipid nanoparticles (SLNs) as a potential anticancer drug delivery system by enhancing its solubility. Methods: SLNs consist of a solid lipid matrix where the drug was incorporated. Surfactants of GRAS grade were used to avoid aggregation and to stabilize the SLNs. DST-SLNs formulations of varying concentrations were prepared by high speed homogenization technique and evaluated for drug excipients compatibility study, poly-dispersity index, particle size analysis, surface morphology, zeta potential and drug release features. Results: It was observed that DST-SLNs with optimum quantities of poloxomer: lecithin ratio showed 88.06% drug release in 6h with good entrapment efficiency of 76.9±0.84 %. Particle size, Poly dispersity index, zeta potential and drug entrapment efficiency for the optimized formulation was found to be optimum. Stability studies revealed that the entrapment efficiency of the SLN dispersion stored in 4 °C was stable. Conclusion: Thus, it can be concluded that formulations of DST loaded SLNs are suitable carriers for improving the solubility and dissolution related problems.